Academic Success And Its Role In Developing Students’ Academic Activities - Turaboye , Madinaxon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The article discusses the important aspects of achieving the quality and effectiveness of education in the conditions of New Uzbekistan. In the modern educational process, student activity and its success are considered the most important result, and in order to achieve the intended goal, the educational process must be effectively organized, which requires great skill and intellectual intelligence from the teacher. In this sense, this article presents proposals and recommendations regarding the success of the student in education and his role in the development of students’ educational activities.